Perspectives on gender in Romania - ILOVAN, Oana-Ramona; SABĂU, Claudia Septimia (Presa Universitară Clujeană, 2023)
This is the first volume of the Collection Gender and Development, coordinated by dr. Oana‐Ramona Ilovan and dr. Georgeta Fodor. The present volume contributes to a better understanding of gender, gender roles and relations in nowadays Romania and in its recent past, highlighting women’s position in society, analysing the cultural stereotypes related to them, the political and cultural mechanisms through which they had been put apart, the pressures they faced, their daily patterns and behaviours. The interdisciplinary profile of all studies gathered in the volume is clear and will be focused on step by step when briefly presenting them. Gender perspectives and insights are present in the historical, anthropological, anthropo-geographical, legislative approaches the volume contains, as well as in those from mobility studies and visual arts.